Strategy and Implementation of Integrating Character Education in Organizational Activities at Muhammadiyah Cipanas Senior High School - Darmawan, Gani; Rochim Maksum, Muh Nur; Ali Mustofa, Triono (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
Responding to the problem of the character education process has not been maximized, as well as to face the challenges of rapid technological advancement that has given birth to globalization and socio-cultural shifts, Islamic programs are expected to have a positive impact on character education, while the Muhammadiyah Student Association is an organization in which it has an Islamic program. This study aims to describe the implementation of character education in the Islamic program of the Muhammadiyah Student Association Branch of Muhammadiyah Cipanas Senior High School, the inhibiting factors, and also the solutions to overcome them. This research uses a qualitative approach, with data collection methods in the form of in-depth observations, interviews, and documentation. The data analysis techniques in this study go through the stages of data reduction, data display, data verification, and conclusion. The results of this study show that the implementation of character education in the Islamic program of the Muhammadiyah Student Association Branch of Muhammadiyah Cipanas High School includes introductory activities such as FORTASI activities, training activities such as PKDTM 1, and routine activities or habituation such as tadarus. The factors that hinder the implementation of character education in the Islamic program of the Muhammadiyah Student Association Branch of Muhammadiyah Cipanas Senior High School are: 1) Focus on Academic Achievement, 2) Lack of Interesting Religious Learning, 3) Popular Culture Influence, 4) Lack of Model Role, 5) Technological Development, 6) Lack of Parental Participation, and 7) Free Association. The solutions are: 1) Integration of Islamic Values in All Subjects, 2) Development of a Creative Religious Curriculum, 3) Improvement of the Quality of Teachers on Religion, 4) Cooperation with Parents, 5) Utilization of Technology, 6) Formation of Communities/Study Groups, 7) Interesting Religious Activities, and 8) Continuous Evaluation.